Antibacterial Activity Test of Sonneratia alba Mangrove Root Infusa Against Propionibacterium acnes and Salmonella typhi Bacteria - Christin, Andriany M.; Mongi, Jeane; Kanter, Jabes W.; Maarisit, Wilmar; pakingki, Priska; Tombuku, Joke L. (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2024)
Infectious diseases can be caused by microbiological agents, namely bacteria. The ability of bacteria to invade and cause infection is referred to as a pathogenicity. The results of phytochemical screening produced secondary metabolite compounds alkaloids, flavonoids, tannins, saponins, phenolics that act as antibacterial. This study aims to determine the antibacterial activity of Sonneratia alba mangrove root infusa against Propionibacterium acnes and Salmonella typhi bacteria. This type of research is a laboratory experimental research, using the well method by doing three repetitions on 5 concentration series, 1 positive control and 1 negative control for two types of bacteria namely Propionibacterium acnes and Salmonella typhi. The results obtained from the Kruskal Wallis test on Propionibacterium acnes bacteria are Sig 0.028 < 0.05, and the results of the ANOVA test on Salmonella typhi bacteria from Sig = 0.000 < 0.05. And it is known in Propionibacterium acnes bacteria that 25% concentration inhibits 5.83 mm, 50% concentration inhibits 6.3 mm, 100% concentration inhibits 9.43 mm. And in Salmonella typhi bacteria that concentration is known that 25% concentration inhibits 9.73 mm, 50% concentration inhibits 9.43 mm, 100% concentration inhibits 11.57 mm. Based on the results of the study, it can be concluded that Sonneratia alba root infusa has antibacterial activity on Propionibacterium acnes and Salmonella typhii bacteria.